Abundance and Diversity of Sea cucumbers in Point Pedro Coastal Waters in Jaffna Peninsula of Sri Lanka - Veronika, K.; Edrisinghe, U.; Sivashanthini, K.; Athauda, A.R.S.B. (University of Jaffna, 2015)
Sea cucumbers are fascinating and commercially valuable species belong to Class Holothuroidea. The present study was conducted with the aim of documenting the species composition and diversity of sea cucumber population in Point Pedro coastal area of Jaffna peninsula. The investigation was carried out from May 2014 to June 2015 at two study sites namely Viyaparimuli and Munnai. Sea cucumbers were collected within random transects areas of 4 m width and 100 m length. All the sea cucumbers were brought to the laboratory and identified up to species level based on the morphological characters and spicule preparation. Standard ecological parameters such as Simpson's Index (D), Shannon index (H) and Evenness index (J) were estimated. A total of four species belong to the Order Aspidochirotida and two each representing Family Holothuriidae and Family Stichopodidae were identified. Among them Holoturiaatra was the dominant species contributing 46.46% of the population followed by S. horrens, S. herrmanni, H. leucospilota representing 32.78%, 17.16% and 3.60%, respectively. The presence of S. horrens, S. herrmanni, H. leucospilota were recorded for the first time in Point Pedro area. According to diversity indices, maximum species diversity, richness and evenness were reported at Munnai site compared to Viyaparimoolai site. The information and observations in this study will be of use in formulating management policies for the sea cucumber fishery in the Point Pedro coastal area.
Keywords: Coastal waters; diversity indices; sea cucumber; species composition